Global Value Chain and the Changing Roles of Country and Industry Effects in International Portfolio Diversification - Song Chen; Rui Yang; Xiaohui Hou; Jingwen Zhao (Complexity)
We find that in the upstream status of global value chain, country effects are relatively stronger than industry effects; industry effects dominate country effects downstream of the global value chain. During financial crisis, downstream in the value chain, the influence of industry effects waned and country effects rose. Moreover, for developed countries, the negative impact of the upstream status of value chain weakened considerably; the impact of upstream status strengthened for emerging markets after the subprime mortgage crisis. For tradable industries, the negative impact of global value chain upstream status on pure industry-specific returns strengthens significantly.